Teaching Macroeconomics and Political Science in Higher Education Using the Sustainable Development Goals - Pastor-García, María Inmaculada; Martínez-Martínez, Ignacio; Rodríguez-Barquero, A. Francisco (Centre for Global Education, 2023)
This article reflects on the outcomes of a three-year teaching innovation project in which Sustainable Development Goals’ (SDGs) content was integrated into a traditional macroeconomics syllabus, and the subjects of Global Governance and Comparative Politics. The project provided training to practising university lecturers on development education and global citizenship education. By including the SDGs in teaching, the effects that certain economic and political decisions can generate in social, environmental and economic terms could be analysed. Under a humanistic approach, some economic and social trends are examined and valued considering the secondary effects that these actions produce, including generating poverty and social injustice. The order and structure of the SDGs offer a conceptual framework that has facilitated critical analysis and understanding of the causes of inequality. In this regard, although the SDGs can be criticised as not being an effective instrument to achieve the goals for which they are designed, they are a useful reference for undergraduates and an efficient teaching resource to simultaneously comply with the delivery of subject content and introduction of development education. This teaching experience allows us to extract various reflections on the results obtained, some of which refer to the teaching activities carried out, and others on university students’ perceptions monitored using a survey. The project improved the training of the participating university lecturers, who acquired greater knowledge, skills and enhanced their teaching practice. The project demonstrated the need of the university to enhance support for sustainability, involving the entire educational community and coordinating planning that contributes to the development of sustainable academic and professional capacities.
https://www.developmenteducationreview.com/about
Keywords: Educación y desarrollo; Desarrollo sostenible; Macroeconomía - Estudio y enseñanza superior; Política - Estudio y enseñanza superior; Development education; Global citizenship education; Higher level education; Sustainable development goals; Economics; Political science